Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/czoolo/57.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Inter-signal interaction and uncertain information in anuran multimodal signals

Abstract: Disentangling the influence of multiple signal components on receivers and elucidating general processes influencing complex signal evolution are difficult tasks. In this study we test mate preferences of female squirrel treefrogs Hyla squirella and female túngara frogs Physalaemus pustulosus for similar combinations of acoustic and visual components of their multimodal courtship signals. In a two-choice playback experiment with squirrel treefrogs, the visual stimulus of a male model significantly increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…The temporal coordination between the acoustic components and visual cues associated with calling (visible inflation of a vocal sac) also influences female responses [46]. Research on the squirrel treefrog, Hyla squirella, found similar cross-modal interactions [47]. Starnberger et al [29] provide an excellent review of additional anuran signalling examples, including those in which temporal coordination among signal elements influences element function.…”
Section: (B) the Dynamic Nature Of Animal Signallingmentioning
confidence: 99%
“…The temporal coordination between the acoustic components and visual cues associated with calling (visible inflation of a vocal sac) also influences female responses [46]. Research on the squirrel treefrog, Hyla squirella, found similar cross-modal interactions [47]. Starnberger et al [29] provide an excellent review of additional anuran signalling examples, including those in which temporal coordination among signal elements influences element function.…”
Section: (B) the Dynamic Nature Of Animal Signallingmentioning
confidence: 99%
“…Furthermore, the results of the visual cues in chorus noise experiment demonstrate that even with the auditory stimulation of a mating chorus, females showed phototaxis but failed to discriminate between visual stimuli. There are many other combinations of auditory and visual stimuli that could be tested, and interactions between these modalities are known to be important in anurans (Narins et al, 2003;Taylor et al, 2011). However, the primary aim of our study was to determine whether females responded to, and discriminated between, visual stimuli alone.…”
Section: Video Playbacks In Anuransmentioning
confidence: 99%
“…Receiver responses can be modulated by interactions among signal components in nonhuman animals as well, sometimes in unexpected ways 2 . Adding to the confusion is that traits conspicuous to humans are sometimes surprisingly unimportant as signal components in nonhuman animals 3 , 4 . Controlling aspects of one perceptual modality and not another would be useful when investigating animal behavior, but is often impossible when working exclusively with living organisms.…”
Section: The Challenges Of Multimodalitymentioning
confidence: 99%